Incorporation of Ca, P, Mg, and Zn Elements in Ti-30Nb-5Mo Alloy by Micro-Arc Oxidation for Biomedical Implant Applications: Surface Characterization, Cellular Growth, and Microorganisms’ Activity - Cardoso, Giovana Collombaro [UNESP]; Barbaro, Katia; Kuroda, Pedro Akira Bazaglia [UNESP]; Imperatori, Luca; De Bonis, Angela; Teghil, Roberto; Curcio, Mariangela; Innocenzi, Elisa; Grigorieva, Victoria Yu.; Vadalà, Gianluca; Grandini, Carlos Roberto [UNESP]; Rau, Julietta V. (MDPI, 2023)
Micro-arc oxidation (MAO) is a surface modification technique used to improve the surface properties of titanium alloys, such as corrosion, wear resistance, and osseointegration. In addition to promoting the growth of a porous oxide coating on the sample’s surface, it is also possible to incorporate bioactive elements into this coating, such as calcium, phosphorus, and magnesium, as well as elements with antimicrobial action, such as zinc. Thus, this study aimed at the surface modification of the β Ti-30Nb-5Mo alloy by the MAO method, incorporating calcium, phosphorus, magnesium, and zinc to improve osseointegration and promote bactericidal character in the produced coating. The results showed that the porosity, roughness, and crystallinity of the coating tend to increase with increasing Zn concentration in the electrolyte, while the contact angle decreases. The antimicrobial activity was promoted against the E. faecalis and P. aeruginosa bacteria strains and the C. albicans fungus. Incorporating Zn on the surface also did not negatively affect adiposetissue-derived mesenchymal stem cell differentiation, and promoted more significant growth of these cells on the samples’ surface.
Keywords: antimicrobial activity; micro-arc oxidation; surface modification; Ti-30Nb-5Mo alloy; titanium alloy; zinc